Respuesta :
Answer:
The correct option is 3.
Step-by-step explanation:
In option 1,
The given equation is
[tex]3x^2-4x-1=(3x+1)(x-1)[/tex]
Simplify the right sides.
[tex]3x^2-4x-1=3x(x-1)+1(x-1)[/tex]
[tex]3x^2-4x-1=3x^2-3x+1x-1[/tex]
[tex]3x^2-4x-1 \neq 3x^2-2x-1[/tex]
Since left hand side is not equal to right hand side, therefore option 1 is incorrect.
In option 2,
The given equation is
[tex]3x^2-2x-1=(3x-1)(x+1)[/tex]
Simplify the right sides.
[tex]3x^2-4x-1\neq 3x^2+2x-1[/tex]
Since left hand side is not equal to right hand side, therefore option 2 is incorrect.
In option 3,
The given equation is
[tex]3x^2-4x+1=(3x-1)(x-1)[/tex]
Simplify the right sides.
[tex]3x^2-4x+1=3x^2-4x+1[/tex]
Since left hand side is equal to right hand side, therefore option 3 is correct.
In option 4,
The given equation is
[tex]3x^2-2x+1=(3x-1)(x-1)[/tex]
Simplify the right sides.
[tex]3x^2-2x+1\neq 3x^2-4x+1[/tex]
Since left hand side it not equal to right hand side, therefore option 4 is incorrect.
Answer:
C 3x2 – 4x + 1 = (3x – 1)(x – 1)
Step-by-step explanation: